(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study is intended to provide basic data on the development of nursing intervention programs to solve the stress of life, the social support, life stress and meaning of life for Climacterium women. Methods/Statistical analysis: The study was conducted by Climacterium women in W city in Gangwon province, collecting data from February 11 to February 22, 2019, and a total of 173 people. Findings: The study found that Climacterium women’s social support was significant in age, education, marriage, occupation, and monthly income, and that life stress was significant in age, education, marriage, and monthly income. The meaning of life was significantly higher in education, marriage, occupation, and monthly income. Social support for Climacterium women showed a negative correlation with life stress, and a significant static correlation with the meaning of life. Economic problems, which are a lower factor of life stress of Climacterium women, have been a factor that has a significant negative impact on the meaning of life. Improvements/Applications: Since Climacterium women play a pivotal role in family life, it is necessary to develop a support program that can measure the level of life and fully play a pivotal role in society as a whole.